Long-Term Efficacy of Systemic Multiexon Skipping Targeting Dystrophin Exons 45-55 With a Cocktail of Vivo-Morpholinos in Mdx52 Mice - Yusuke Echigoya; Yoshitsugu Aoki; Bailey Miskew; Dharminder Panesar; Aleksander Touznik; Tetsuya Nagata; Jun Tanihata; Akinori Nakamura; Kanneboyina Nagaraju; Toshifumi Yokota (Elsevier, 2015)
Antisense-mediated exon skipping, which can restore the reading frame, is a most promising therapeutic approach for Duchenne muscular dystrophy. Remaining challenges include the limited applicability to patients and unclear function of truncated dystrophin proteins. Multiexon skipping targeting exons 45-55 at the mutation hotspot of the dystrophin gene could overcome both of these challenges. Previously, we described the feasibility of exons 45-55 skipping with a cocktail of Vivo-Morpholinos in vivo; however, the long-term efficacy and safety of Vivo-Morpholinos remains to be determined. In this study, we examined the efficacy and toxicity of exons 45-55 skipping by intravenous injections of 6 mg/kg 10-Vivo-Morpholino cocktail (0.6 mg/kg each vPMO) every 2 weeks for 18 weeks to dystrophic exon-52 knockout (mdx52) mice. Systemic skipping of the entire exons 45-55 region was induced, and the Western blot analysis exhibited the restoration of 5-27% of normal levels of dystrophin protein in skeletal muscles, accompanied by improvements in histopathology and muscle strength. No obvious immune response and renal and hepatic toxicity were detected at the end-point of the treatment. We demonstrate our new regimen with the 10-Vivo-Morpholino cocktail is effective and safe for long-term repeated systemic administration in the dystrophic mouse model.